Pemanfaatan Asap Cair dari tempurung Kelapa sebagai pengawet dalam Proses Pengolahan Ikan Layang (decapterus sp) yang Berada di Perairan Gorontalo - Riskawati Pomolango; Ishak Isa; Hendri Iyabu (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This research aims to analyze the effect of storage duration on the quality of flying fish soaked in coconut shell liquid smoke. The main focus of the research includes testing water and phenol content, as well as evaluating the resistance of liquid smoke to sensory qualities, such as taste, aroma and texture of flying fish. The research used liquid smoke with varying concentrations of 0%, 3%, 5% and 7%, with a soaking time of 30 minutes. Data analysis was carried out using SPSS version 26 with the ANOVA test method. The results showed that the addition of liquid smoke with different concentrations had a significant influence on water content, phenol content and organoleptic parameters of flying fish.